2014
DOI: 10.1089/brain.2014.0295
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Effective Connectivity from Cortices to the Right Parahippocampal Gyrus in Alzheimer's Disease Subjects

Abstract: The purpose of this study was to detect effective connectivity (EC) changes in the default mode network and hippocampus network in 20 patients with Alzheimer's disease (AD) and 20 cognitively normal (CN) subjects, using multivariate Granger causality. The authors used the maximum coefficients in the multivariate autoregression model to quantitatively measure the different EC strength levels between the CN and AD groups. It was demonstrated that the EC strength difference can classify AD from CN subjects. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…Previous studies have found the right parahippocampal gyrus showed imbalanced bidirectional effective connections in the default mode network (DMN) and hippocampus network. Along with our findings as the morphological evidence, it may provide neurophysiological explanations for AD patients’ memory impairment during the encoding processes [47]. Besides, it should be noted that the majority of our positive results were inclined to the right side.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have found the right parahippocampal gyrus showed imbalanced bidirectional effective connections in the default mode network (DMN) and hippocampus network. Along with our findings as the morphological evidence, it may provide neurophysiological explanations for AD patients’ memory impairment during the encoding processes [47]. Besides, it should be noted that the majority of our positive results were inclined to the right side.…”
Section: Discussionsupporting
confidence: 86%
“…PSEN1 mutation carriers did not show reduced functional connectivity when compared with noncarriers, as previously reported in the later preclinical and clinical stages of AD. 21-23 …”
Section: Resultsmentioning
confidence: 99%
“…Chen et al also found that the right parahippocampal gyrus showed imbalanced bidirectional effective connections in AD patients, which received weaker input connections from the neocortices, although output connections were significantly increased. 58 The FC between the parahippocampal gyrus and the PCC is known to be reduced in AD patients and becomes more severely damaged as the disease progresses. 59 Conversely, previous studies have detected gray matter reduction and diffusion tensor MRI abnormalities in the right parahippocampal gyrus in MDD.…”
Section: Discussionmentioning
confidence: 99%